Quale Terzo Settore dopo la L. 104 del 2024? L’importanza di un’agenzia indipendente per tutto il No Profit (Società e diritti, 2024)
This paper examines the Third Sector concept from sociology and general theory of law, with a focus on its inconsistencies and anomalies in light of the latest laws on this topic.The author concludes by calling for a new independent agency for non-profit organizations, which confers new coherence to the relationship between non-profit organizations and third-sector entities, and goes beyond the current bureaucratic method of regulation to make room for autonomy, self-determination, and self-organization of civil society.